Application of Jigsaw Learning Model on Recount Text to Enhance Writing Ability - Khumairoh, Nabila Putri; Muhtarom; Datik, Aisyiyah Munawar (ICONELT, 2024)
This study is focused on finding out the implementation of the jigsaw learning model to enhance students’ abilities in writing recount text in classroom VIII A UPT SMPN 2 Gresik. The jigsaw learning model is a cooperative activity technique with a group learning approach. The effectiveness of the jigsaw learning model is that learners can engage more actively in sharing feedback in expert groups before returning and presenting the result to the original group. From these learning activities, they get the results from their discussion. This research uses a qualitative and quantitative method obtained from a research sample of class VIII A students at UPT SMPN 2 Gresik. The collected data is qualitative use of data taken using test results for writing English recount text, while the source of qualitative data is the observation results of the jigsaw learning model with the jigsaw learning model, The process carried out by research and collaborators, The research results on applying the use of the jigsaw learning model in classroom activities show a positive response that they understand the material, From these result, it shows that the use of the jigsaw type of learning model is effective and has a very positive effect on the learning and performance of the student to improving recount text writing skills, This is following the outcome of observation a student learning in 1st cycle with the highest value range (56.25%) to (93.75%) of students and from cycle II. Students look more active and enthusiastic when working on group assignments.